Concise synthesis of the C15–C38 fragment of okadaic acid, a specific inhibitor of protein phosphatases 1 and 2A. Issue 37 (16th September 2015) - Fuwa, Haruhiko; Sakamoto, Keita; Muto, Takashi; Sasaki, Makoto
Abstract: A marine polyether natural product okadaic acid is known to be a potent and specific inhibitor of protein phosphatases 1 and 2A. Herein, concise synthesis of the C15–C38 fragment of okadaic acid is reported. We investigated two different strategies for the construction of two spiroacetal substructures found in the target compound. The first strategy involved Suzuki–Miyaura coupling for the synthesis of endocyclic enol ethers and subsequent spiroacetalization. The second strategy exploited Suzuki–Miyaura coupling for the synthesis of exo -olefins as the precursor of spiroacetals. An alkynylaluminum–anomeric sulfone coupling effectively assembled the key spiroacetal substructures and completed the target compound. Graphical abstract: